2022
DOI: 10.31127/tuje.818539
|View full text |Cite
|
Sign up to set email alerts
|

A statistical investigation to determine dominant frequency of layered soil profiles

Abstract: Energy based seismic design Layered soil profile Fundamental period ResonanceEnergy based seismic design getting attraction since it accounts for all structural (hysteretic behavior of structural members), earthquake (amplitude, duration and frequency content) and soil (bearing capacity, frequency content) characteristics. To develop an efficient energy based seismic design procedure, accurate determination of the fundamental periods of the soil deposits is crucial. Hence, several analytical, numerical and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, as mentioned above, this equation overestimates the fundamental site period by 20%. Therefore, Güllü and Hasano glu [106] proposed a best-fit coefficient for the total travel time, which resulted in a minimum standard deviation for 459 KiK-net stations. The study proposed a simple yet more accurate equation based on statistical analyses, as shown in Equation (25).…”
Section: Data-driven Methodsmentioning
confidence: 99%
“…However, as mentioned above, this equation overestimates the fundamental site period by 20%. Therefore, Güllü and Hasano glu [106] proposed a best-fit coefficient for the total travel time, which resulted in a minimum standard deviation for 459 KiK-net stations. The study proposed a simple yet more accurate equation based on statistical analyses, as shown in Equation (25).…”
Section: Data-driven Methodsmentioning
confidence: 99%